Wetland Resource Utilization By Spot-Billed Pelicans In Coimbatore, Tamil Nadu - Leo , Theresa; Velayutham, Meiyalagan (Kongunadu Research Journal, 2019)
The Spot-billed Pelican (Pelecanus philippensis), a near threatened bird and one of eight pelican species in the world, can be found only in South and Southeast Asia over an area between 129000 and 181000 km2 with strongholds in India, Sri Lanka, southern Cambodia and coastal areas of Sumatra. In India,it is presently distributed in southern and northeastern India with concentrations in Andhra Pradesh, Tamil Nadu, Karnataka and Assam states. The present study deals how the spot- billed pelicans utilize the wetlands as well as their behaviour is noted in order to plan conservation and management strategies for the species.